Flipped Classroom Method in enhancing Computer Self-Efficacy among pre service teachers - Midhun Moorthi C (AG Volumes, 2023)
The goal of flipped classroom strategy is to make better use of class time via a more interactive, student-centered method. Many academic fields have lately been interested in this method, which has traditionally been used in Physical Sciences. The rapidly spreading practice of flipping the classroom is not yet widely accepted in the United States. The objective of the research is to highlight its usefulness in the classroom and get wider recognition among academics. To that end, the research examined the flipped classroom method and its benefits and drawbacks, as well as the technological models that support it. Increased teacher-student connection, flexibility in when and where students may access course materials, time savings (especially during practice), a more student-centered approach, and higher levels of engagement are just a few of the many benefits of flipped classroom paradigm. There are various issues with this approach as well. Technology needs, lack of video viewing, low class attendance, and less student-teacher engagement, particularly in non-classroom settings, are all factors.